ANALISIS KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA CV HELDA TRAVEL BERSAUDARA SANGATTA - riduansah riduansah; Triska Aprilo (Jurnal Eksis, 2020)
This study aims to analyze the effect of service quality on customer satisfaction at the company Helda Travel Brothers Sangatta. This study uses 5 (five) independent variables / independent variables, namely direct evidence, reliability, responsiveness, assurance, and empathy with one dependent variable / dependent variable, namely customer satisfaction. This research refers to several literature reviews and field studies The data in this study were collected through distributing questionnaires to 40 respondents who became samples and observations. The sampling technique used was purposive sampling. The data analysis method used is quantitative analysis, namely validity, reliability, classical assumption test, multiple linear regression analysis, t test, coefficient of determination and f test.Based on data analysis, the results showed that the indicators in this study were valid and reliable. In the classical assumption test, data is normally distributed, heteroscedasticity and multicollinearity do not occur. In the hypothesis test, it shows that the direct evidence variable has a positive effect but does not have a significant effect on customer satisfaction, the reliability variable has a negative effect and does not have a significant effect on customer satisfaction, the responsiveness variable has a positive effect but does not have a significant effect on customer satisfaction. has a positive effect there is no significant effect on customer satisfaction, the variable empathy has a positive effect but does not have a significant effect on customer satisfaction and simultaneously there is an effect of direct evidence, reliability, responsiveness, assurance, and empathy on customer satisfaction. Keywords: Direct Evidence, Reliability, Responsiveness, Assurance, Empathy and Customer Satisfaction